2008
DOI: 10.1007/s00259-008-0932-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid uptake of 67Ga-citrate is associated with thyroid autoimmunity and hypothyroidism in patients with sarcoidosis

Abstract: (67)Ga thyroid uptake is associated with the presence of aggressive autoimmune thyroiditis and hypothyroidism in S patients; thyroid function and ultrasonography should be performed in the presence of (67)Ga thyroid uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…20 Data derived from larger studies have not shown positive TRAbs in sarcoidosis. 12 However, our findings show a significantly higher frequency of TRAbs in sarcoidosis patients compared to gendermatched controls. Moreover, in our study the presence of TRAbs was almost unequivocally associated with ultrasonographic signs of thyroid autoimmunity (dyshomogeneous thyroid parenchyma).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…20 Data derived from larger studies have not shown positive TRAbs in sarcoidosis. 12 However, our findings show a significantly higher frequency of TRAbs in sarcoidosis patients compared to gendermatched controls. Moreover, in our study the presence of TRAbs was almost unequivocally associated with ultrasonographic signs of thyroid autoimmunity (dyshomogeneous thyroid parenchyma).…”
Section: Discussioncontrasting
confidence: 53%
“…8 Controversy also exists regarding the presence of thyroid antibodies in sarcoidosis patients, with studies pointing to increased prevalence of antithyroid peroxidase antibodies (TPOAbs) and antithyroglobulin antibodies (TGAbs) 10 in sarcoidosis patients, while others have failed to document any differences. 11 Data concerning TSH receptor antibodies (TRAbs) are rather scarce, most of them derived from case reports; meanwhile, in a prospective study by Antonelli et al 12 the authors failed to demonstrate increased TRAbs titles in sarcoidosis. Thus, currently no definite conclusions can be drawn regarding the association of sarcoidosis with thyroid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, she had elevated thyroid peroxidase antibodies which is also well documented in various studies. [ 9 10 ] While the hypothyroid and euthyroid state in Hashimoto's thyroiditis is well known and such a diagnosis has therapeutic and prognostic implications; complete thyroid function tests done were, however, normal. The patient was explained regarding her basic disease predispositions and advised close follow-up for the recurrence of primary disease and development of other autoimmune manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the association of Ga-67 citrate thyroid uptake with thyroid disorders in S patients, 84 subjects were evaluated by ultrasonography, serum thyroid hormones and antithyroid antibodies, and FNA ( 11 ).…”
Section: Thyroid Autoimmunity and Sarcoidosismentioning
confidence: 99%
“…Sarcoidosis is associated with autoimmunity such as autoimmune thyroid disorders (AITDs) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%